"Walking in Their Shoes": The effects of an immersive digital story intervention on empathy in nursing students. Issue 5 (20th March 2021) - Yu, Juping; Parsons, Gareth S; Lancastle, Deborah; Tonkin, Emma T; Ganesh, Siva
Abstract: Aim: To evaluate the effects of a novel, immersive digital story intervention on empathy. Design: A randomized trial with three phases. Results: A total of 238 2nd year nursing students were recruited between May 2018 and December 2019. At baseline, no significant differences in empathy between the groups were found ( p  = .760). However, at post‐test, empathy was significantly higher in the intervention group (M: 118.76, SD : 10.65) than it was in the control group (M: 114.60, SD : 15.40) ( p  = .012). At follow‐up, there were no significant differences in empathy between the groups ( p  = .364). Conclusion: The intervention resulted in an immediate increase in empathy in nursing students. However, further development of effective intervention delivery modes and fundamental redesign of the intervention itself would be needed to sustain this improvement over the long term.